2015
DOI: 10.5194/cpd-11-4895-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An astronomical correspondence to the 1470 year cycle of abrupt climate change

Abstract: Abstract. The existence of a ~ 1470 year cycle of abrupt climate change is well-established, manifesting in Bond ice-rafting debris (IRD) events, Dansgaard–Oeschger atmospheric temperature cycle, and cyclical climatic conditions precursory to increased El Niño/Southern Oscillation (ENSO) variability and intensity. This cycle is central to questions on Holocene climate stability and hence anthropogenic impacts on climate (deMenocal et al., 2000). To date no causal mechanism has been identified, although solar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The pattern in the pollen sections with high-resolution may be the botanical counterpart to the 1500-year cyclicity also known from other paleoclimate archives, e.g., the timing of interstadials from Greenland ice cores during MIS 5 to 3 [62][63][64], monsoon intensification during the last deglaciation [65], and Holocene ice-rafted debris (IRD) events [66,67]. The 1500-year cyclicity appears to be highly regular in the annually laminated ice cores and, thus, most likely does not originate in the Earth's system but must be triggered by orbital parameters [62,68], possibly the sun [69]. Other studies question the existence of such a cyclicity in Greenland ice δ 18 O, since in statistical significance tests, the proposed periodicity was not distinguishable from random noise [70].…”
Section: Eifel Vegetation Patterns From 132000 Yr B2k Until Present: ...mentioning
confidence: 96%
“…The pattern in the pollen sections with high-resolution may be the botanical counterpart to the 1500-year cyclicity also known from other paleoclimate archives, e.g., the timing of interstadials from Greenland ice cores during MIS 5 to 3 [62][63][64], monsoon intensification during the last deglaciation [65], and Holocene ice-rafted debris (IRD) events [66,67]. The 1500-year cyclicity appears to be highly regular in the annually laminated ice cores and, thus, most likely does not originate in the Earth's system but must be triggered by orbital parameters [62,68], possibly the sun [69]. Other studies question the existence of such a cyclicity in Greenland ice δ 18 O, since in statistical significance tests, the proposed periodicity was not distinguishable from random noise [70].…”
Section: Eifel Vegetation Patterns From 132000 Yr B2k Until Present: ...mentioning
confidence: 96%
“…Global ~1000 [18] Millennial-scale climatic oscillations of ~1,470 years are evident in numerous palaeo-climatic records in the North Atlantic and Pacific [67 -71]. A study [72] discussed the existence of a ~ 1,470 year cycle in the context of climate change. Another [67] concluded from studies of the ratio of iron-stained to clean grains in ice-rafted debris in North Atlantic sediments, that climatic conditions have oscillated with an average period ~1,500 years over the past 100,000 years of the Holocene…”
Section: Millennial Scale Periodicitiesmentioning
confidence: 99%
“…Other studies [72] have discussed the existence of a ~1,470 year cycle of associated with climate change and the possible origins of the cycle, incorporating orbital, solar and lunar forcing.…”
Section: Solar Origin Of Oscillationsmentioning
confidence: 99%
“…Furthermore, atmospheric processes like the North Atlantic Oscillation (NAO), described as the major forcing behind moisture penetration, North Atlantic westerlies position and the consequent penetration of winter storm tracks into the western Mediterranean region (Hurrel 1995;Trigo et al 2004), has been suggested as millennial-scale phenomenon controlling the ~1500 year cycle (Thompson and Wallace 2001;Debret et al 2007). Recently, this cycle has also been interpreted as a high frequency extension of the Milankovitch precessional cycles, incorporating orbital, solar and lunar forcing through interaction with the tropical and anomalistic years and the Earth's rotation (Kelsey et al 2015). Thus, a single theory explaining the formation of this cycle does not exist, and it is interpreted as caused by a combination of several forcing mechanisms (Wanner and Bütikofer 2008;Wanner et al 2011Wanner et al , 2015Smith et al 2016, and references therein).…”
Section: Introductionmentioning
confidence: 99%